The Application of Recycled Materials in Construction Building : A Brief Review - Ahmad, Nor Farah Atiqah; Ahmad, Siti Hamizah; Mokhtarruddin, Muhd Ikmal Eizzat; Sapian, Siti Najihah (Multidisciplinary Applied Research and Innovation, 2020)
Excessive and uncontrolled production of waste will have a detrimental effect on nature. Due to that, the concept of 3R (reuse, reduce, recycle) was introduced as early as 1976. Recycling is the process of converting waste into new materials or objects that can be used. This study focuses on the application of recycled materials in construction materials and discover the alternative measures in recycled materials. The waste management depends on the type of waste and the recycled product from the waste. The most distinguish result from recycling process are development of sustainable concrete, pavement, and even thermal insulation on buildings. Based on the review study, waste management encourage to recycled and reuse in order to minimize the environmental pollutions.